A comparison of women with child‐adolescent versus adult onset binge eating: Results from the National Women's Study. Issue 7 (5th June 2014) - Brewerton, Timothy D.; Rance, Samantha J.; Dansky, Bonnie S.; O'Neil, Patrick M.; Kilpatrick, Dean G.; Weissman, Ruth Striegel; Klump, Kelly; Steiger, Howard; Tanofsky‐Kraff, Marian
ABSTRACT Objective Studies of age of first binge have been conducted in clinical samples of patients with bulimia nervosa (BN) and binge eating disorder (BED), but few studies have examined age of first binge using nationally representative samples. Method We examined age of first binge and its clinical correlates using data generated from the National Women's Study (n = 3, 006). Participants who endorsed ever binge eating (n = 707) were divided into two groups: (1) child‐adolescent onset (CO)—age of first binge <18 years, and (2) adult onset (AO)—age of first binge ≥18 years. We hypothesized that CO binge eating would be associated with greater (1) likelihood of developing BN/BED, (2) severity of BN/BED, (3) history of trauma and PTSD, and (4) history of psychiatric comorbidity, such as major depression and substance use. Results Of those who ever endorsed binge eating, 212 reported CO (30%) and 495 (70%) reported AO. Although AO binge eating was more common, CO binge eating was associated with higher rates of lifetime BN, greater severity of bulimic symptoms, earlier age of first dieting; earlier age at highest weight, greater likelihood of ED treatment, and higher rates of molestation, physical assault, any direct victimization, lifetime PTSD, and substance abuse. Conclusions AO binge eating is more than twice as common as CO binge eating in women, but CO binge eating is associated with higher rates of lifetime BN, greater severity of BN, and higher rates of victimization, PTSD, and substance abuse. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:836–843)